Case Report: Omicron BA.2 Subvariant of SARS-CoV-2 Outcompetes BA.1 in Two Co-infection Cases - Gjorgjievska, Marija; Mehandziska, Sanja; Stajkovska, Aleksandra; Pecioska-Dokuzovska, Slavica; Dimovska, Anica; Durmish, Idriz; Ismail, Sara; Pavlovska, Teodora; Stojchevska, Antonija; Amedi, Haris; Andonova, Jasna; Nikolovska, Marija; et al. (Frontiers in Genetics, 2022)
Trends from around the world suggest that the omicron BA.2 subvariant is increasing in proportion to the original BA.1 subvariant. Here we report two cases of co-infection with omicron BA.1 and omicron BA.2 in co-exposed individuals. In both individuals, genome sequencing and/or S-gene specific PCR identified omicron BA.1 at early time-points, which was replaced by omicron BA.2 at later time-points of the infection. The timeline of our data supports the proposition that BA.2 outcompetes BA.1 in a real-life scenario, and in time becomes the dominant variant in the upper respiratory tract of the host.